KEHIDUPAN MASYARAKAT ADAT KAMPUNG BANCEUY: KEBERTAHANAN ADAT ISTIADAT MENGHADAPI PERUBAHAN SOSIALBUDAYA (Kajian Historis Tahun 1965-2008) - Selma Nurul Afifah; Syarif Moeis (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This study aims to explain the development of the villager life’s from Banceuy traditional hamlet which is very different from other villager in generals. Banceuy traditional hamlet are one of the society located in Subang that still retains their ancestor’s tradition or custom. The 43 years span show that The Banceuy traditional villagers have gone through so many changes especially in socio-cultural field. The changes happened as time of historical goes on in traditional Banceuy villagers themselves. These changes are influenced by external and internal factors, there are some factors that encourage and inhibit the changes. In this case effects some changes in the value that is not inherent. While the inherent value which is the tradition in Banceuy villagers always kept well reserved with the changes of the era.